THE POSSIBILITY OF TEIL IN INDONESIA - Faizatul Istiqomah (Jurnal Bahasa Lingua Scientia, 2012)
The English teaching in Indonesia so far has been well known as the Teaching English as A Foerign Language in Indonesia (TEFLIN). The successful of the teaching English as a foerign language has been debated among the English practitioners and teachers. Although the English curriculum has been revised many times and the new teaching methods have been introduced and trained to the teachers, it seems that the result is still unsatisfactory. One proposed effort here to make a successful English teaching and learning in Indonesia is by introducing the Teaching English as International Language (TEIL) in Indonesia. This article discusses the possibility of TEIL in Indonesia.